1999
DOI: 10.1086/315022
|View full text |Cite
|
Sign up to set email alerts
|

A Subunit Cytomegalovirus Vaccine Based on Recombinant Envelope Glycoprotein B and a New Adjuvant

Abstract: A phase I randomized, double-blind, placebo-controlled trial was done with a cytomegalovirus (CMV) vaccine based on the envelope glycoprotein, gB, combined with a novel adjuvant, MF59. Participants received CMV gB vaccine with MF59 or CMV gB with alum or placebo at 0, 1, and 6 months. A fourth vaccine was given at 12 months to a subgroup. Levels of neutralizing antibody and antibody to gB 2 weeks after the third dose of vaccine exceeded those in seropositive control subjects. the formulation with MF59 was more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
131
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(137 citation statements)
references
References 18 publications
6
131
0
Order By: Relevance
“…51 Subunit vaccines incorporating only pp65, IE-1, and gB have been developed and elicit both T-cell and antibody responses. 52,53 Studies to identify the viral genes that encode additional CMV antigens recognized by CD8 ϩ CTLs and to elucidate their role in protective immunity should provide insights into the necessity to incorporate additional determinants in a CMV vaccine. …”
Section: Discussionmentioning
confidence: 99%
“…51 Subunit vaccines incorporating only pp65, IE-1, and gB have been developed and elicit both T-cell and antibody responses. 52,53 Studies to identify the viral genes that encode additional CMV antigens recognized by CD8 ϩ CTLs and to elucidate their role in protective immunity should provide insights into the necessity to incorporate additional determinants in a CMV vaccine. …”
Section: Discussionmentioning
confidence: 99%
“…Although a larger numbers of Mmu are needed to conWrm this observation, it further indicates the protective role of neutralizing antibodies against CMV [14,17,18,24] and a gB-based vaccine strategy [15,17,25]. Natural immunity studies have suggested that a vaccine that stimulates immunity equivalent to levels associated with natural infection could reduce the morbidity due to congenital CMV infection by »80% [8,9].…”
Section: #6 Controlmentioning
confidence: 93%
“…Preliminary results from human Phase I trials of recombinant gB vaccine suggest that the vaccine is safe and immunogenic. [47][48][49] While promising, these vaccines have yet to proceed past initial safety trials.…”
mentioning
confidence: 99%